Polycystic kidney disease in a Himalayan-Persian crossbreed cat - Nugraha , Putri; Convienna; Dewa , Andreas Topan; Putra , I Putu Cahyadi; Widyasanti , Ni Wayan Helpina (ARSHI Veterinary Letters, 2025)
Polycystic Kidney Disease (PKD) is a genetic disorder caused by mutations in PKD1, predominantly found in Persian cats. This case study reports the incidence of PKD in a Himalayan-Persian crossbreed cat treated with fluid therapy, renal supplementation, nutritional management, and red mold rice. A 5-year-old spayed female Himalayan-Persian breed cat was brought to the Kassiti Vetcare Veterinary Clinic, Bandung, complaining of decreased appetite for a week, unwilling-ness to eat for four days, abdominal pain, and orange urine. Hyperchromic macrocytic anemia was observed in a complete blood test. Blood chemistry examination revealed increased creatinine levels (363.1 µmol/L), indicating impaired renal function. Ultrasound examination showed that the kidneys were enlarged, the border between the cortex and medulla was unclear, and hypo-to-anechoic cysts of various sizes were observed in the renal cortex-medulla area. The patient was diagnosed with PKD and had poor prognosis. Treatment included intravenous (IV) Ringer’s lactate fluid therapy, RenaCor® renal supplement, Flozindo® red mold rice (RMR), and NatureBridge® for cat kidney. The patient’s condition improved after treatment, as indicated by her active condition and normal urine color.